2020
DOI: 10.1136/archdischild-2020-319063
|View full text |Cite
|
Sign up to set email alerts
|

How to use the Bayley Scales of Infant and Toddler Development

Abstract: The Bayley Scales of Infant and Toddler Development—Third Edition (Bayley-III) is a gold standard series of behavioural assessments used by clinicians and researchers to assess the developmental functioning of young children. The rigorous psychometric properties of the tool are attributed to the carefully standardised normative sample and quantitative scoring system. It is a common end-point assessment used in neonatal trials and is routinely used in a clinical setting to assess the development of children at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(60 citation statements)
references
References 13 publications
2
50
0
Order By: Relevance
“…BSID III is considered the gold standard developmental assessment tool for this age group. 36,37 Early identification of developmental delay is critical as early intervention may ameliorate subsequent neurodevelopmental impairment. 38 Most of the infants in this study had BSID III scores within the normal range at one and two years of age.…”
Section: Discussionmentioning
confidence: 99%
“…BSID III is considered the gold standard developmental assessment tool for this age group. 36,37 Early identification of developmental delay is critical as early intervention may ameliorate subsequent neurodevelopmental impairment. 38 Most of the infants in this study had BSID III scores within the normal range at one and two years of age.…”
Section: Discussionmentioning
confidence: 99%
“…A protocol for the collection, measurement, and interpretation of data was discussed and defined before starting the study. It has been demonstrated that BSID-III tends to underestimate neurodevelopmental delay compared with other scales [49]. However, measurement of NDV using different scales, exploring further domains other than those evaluated by BSID, could overcame this bias.…”
Section: Discussionmentioning
confidence: 99%
“…Reduced perioperative variability in NIRS values is also believed to be a sign of impaired cerebral vascular autoregulation and has been found to be associated with poor neurodevelopmental outcomes at 21 months of age in a mixed population of neonatal cardiac surgery patients [ 20 ]. Neurodevelopmental assessment in that study consisted of the Bayley scales of infant development, which is a standard series of developmental play tasks that derive developmental quotient scores in different domains that can be compared to norm scores obtained from typically developing children of the same age [ 21 ].…”
Section: Reviewmentioning
confidence: 99%